Štajerske dvorne službe do leta 1311 - Bele, Martin (Studia Historica Slovenica, 2021)
The subject of the present article are the Styrian court offices (marshal, chamberlain, seneschal, cup-bearer) that different officials held before the year 1311. Most of the holders of these offices were of noble origin, some of them were citizens of cities. Rare individuals held the same position multiple times (with intervals), which depended of the current political situation. The purpose of the research was mostly to make detailed lists of the office holders and to present them according to their geographical origin. The sources considering the offices in question are unsteady, consequently the outcome also differs from case to case.
Keywords: Bela IV of Bohemia; Bela IV of Hungary; Bela IV.; chamberlain; cup-bearer; Duchy of Styria; komornik; marshal; maršal; Otokar II of Bohemia; Otokar II. Přemysl; Přemysl, Otokar II.; seneschal; stolnik; točaj; vojvodina Štajerska